THE ROLE OF LAVENDER IN MEDICINE - Dzhuraeva Mahbuba Khidirovna; Pulatova Durdona Keldishevna (Web of Journals Publishing, 2025)
The article describes the spread and medicinal properties of lavender plant, its medicinal properties with a wonderful smell, its use in the food industry, cosmetology and perfumery, and medicine.
Keywords: Lavender, flower, medicinal, distribution, cosmetology, perfumery